2010
DOI: 10.1016/j.sdentj.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The use of mini-implants in en masse retraction for the treatment of bimaxillary dentoalveolar protrusion

Abstract: This case report describes the treatment of a 22-year-old girl who had incompetent lips with severe bimaxillary dentoalveolar protrusion. The treatment of choice for such patients is usually extraction of four first premolars and retraction of the anterior teeth. To maintain the extraction space, maximum anchorage is required. Mini-implants were used to provide maximum anchorage for obtaining a good facial profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In the present investigation, the upper anterior teeth of bimaxillary patients were mainly retracted with bodily movement, interpreted as en masse retraction provided by miniscrews (Aljhani and Zawawi, 2010). The controlled tipping movement is a favorable pattern but might induce more obvious dehiscence during retraction of the protruded maxillary incisors (Årtun and Urbye, 1988), which needs to be further verified.…”
Section: Discussionmentioning
confidence: 70%
“…In the present investigation, the upper anterior teeth of bimaxillary patients were mainly retracted with bodily movement, interpreted as en masse retraction provided by miniscrews (Aljhani and Zawawi, 2010). The controlled tipping movement is a favorable pattern but might induce more obvious dehiscence during retraction of the protruded maxillary incisors (Årtun and Urbye, 1988), which needs to be further verified.…”
Section: Discussionmentioning
confidence: 70%
“…During the last 2 decades, numerous studies have reported the success and acceptance of mini-implants in facilitating orthodontic mechanics. 5 , 6 , 25 In this respect, orthodontic treatment has been increasingly affected by the success, or failure of orthodontic mini-implants due to the increasing frequency of their use. 26 , 27 In a clinical situation, during mini-implant placement, a patient under minimum infiltration anesthesia could still feel discomfort during insertion of mini-implant, if it contacts the adjacent root surface, and the practitioner can easily change the placement direction to minimize root contact.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographs used in the current study were for mini-implants inserted distal to the maxillary canine because this is considered a preferable site and ease of accessibility for various orthodontic mechanics. 5 , 6 , 8 , 29 , 30 Moreover, the current study assessed the actual final position of mini-implants in relation to the root proximity using CBCT, which previously could not be carried out using conventional 2D, radiographs. 16 The CBCT data allowed for accurate localization of the mini-implant position and assessment with regard to bone contact, bone penetration, and iatrogenic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The orthodontic (mini)implants simplify the biomechanics in multiple situations and, in terms of anchorage, they eliminate the need for auxiliary appliances [1,2,3]. The literature regarding orthodontic implants is extensive, and their introduction respresents a revolution in orthodontic strategy [1,2,3,4,5,6,7,8]. Treatment planning must include radiographic examination for an accurate placement position.…”
Section: Introductionmentioning
confidence: 99%